A novel blended and interprofessional approach to pediatric emergency training: self-assessment, perception, and perceived long-term effects - Lehmann, Ronny; Klinke Petrowsky, Michaela; Seitz, Anke; Meyburg, Jochen; Eppich, Walter; Hoffmann, Georg F.; Tönshoff, Burkhard; Huwendiek, Sören (BMC medical education, 2024)
We developed a blended training program at a tertiary pediatric center based on hospital-specific emergency guidelines, profession-specific Virtual Patients (VPs), and interprofessional team training. Using this novel approach, we addressed differing educational needs of medical and nursing staff and intrinsic cognitive overload among participants, aiming for harmonization of in-house emergency proceedings. Self-assessments of pediatric emergency knowledge and skills were conducted before (T1) and after (T2) preparation using VPs, as well as after the team training day (T3). At T3, participants completed questionnaires on the training approach, its components, and learning impact. Ten months after the training, a follow-up survey (T4) queried perceived benefits within and beyond emergency situations. A total of 56 medical staff and 56 nursing staff members participated in the pilot phase. Of these, N = 55 (98%) and N = 48 (85%), respectively, returned self-assessments; questionnaires were completed by N = 55 (98%) and N = 51 (91%), respectively. In both groups, 57 participants (50.9%) completed the follow-up survey. After team training (T3), both groups had statistically significant increased knowledge and skill scores compared with those at T1. Regarding the blended approach and its components, medical and nursing staff alike rated the entire course and its guidelines, the preparatory VPs, and the team training very highly. Participants felt being better prepared for pediatric emergencies. Perceived strengths of the training approach were in the triangulation of teaching methods and its interprofessionalism. More training scenarios were requested, as well as recurrent training. In the follow-up, participants reported improved confidence and calmness, as well as improved communication and collaboration when involved in an emergency. Beyond emergencies, benefits were reported in daily routines. Our blended approach was perceived as being effective in improving preparedness among medical and nursing house staff. This approach permits customization of content and deliberate practice to improve pediatric critical care.